1992
DOI: 10.1007/bf00145361
|View full text |Cite
|
Sign up to set email alerts
|

Concept of an antiatherosclerotic efficacy of calcium entry blockers

Abstract: Animal experiments suggest an inhibitory effect of calcium entry blockers on arterial calcinosis and the formation of atherosclerotic plaques. Experiments with isolated tissues suggest various mechanisms for an antiatherosclerotic effect of calcium entry blockers. INTACT, the International Nifedipine Trial on Antiatherosclerotic Therapy, is the first study investigating, with a prospective, placebo-controlled, randomized, double-blind design, the influence of a calcium entry blocker (nifedipine 80 mg/day) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The increase in the cross sectional area was accompanied by a reduced cell count in the different layers of the vessel wall ( Table 2) and although we could not show a reduced cellular proliferation in the treatment group after 3 days a reduced number of SMC layers in the neointima 28 days after BA compared with placebo animals could be detected. Many studies show a beneficial effect of calcium antagonists on the progression of atherosclerosis [21,22]. In animal models various calcium antagonists modified neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in the cross sectional area was accompanied by a reduced cell count in the different layers of the vessel wall ( Table 2) and although we could not show a reduced cellular proliferation in the treatment group after 3 days a reduced number of SMC layers in the neointima 28 days after BA compared with placebo animals could be detected. Many studies show a beneficial effect of calcium antagonists on the progression of atherosclerosis [21,22]. In animal models various calcium antagonists modified neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 98%
“…74,75 Some small clinical trials have confirmed these results in the coronary arteries in humans. In placebo-controlled trials, nifedipine was shown to reduce the number of newly formed coronary lesions in early stage coronary artery disease, 76 but not instable angina pectoris, 77 and to slow down coronary artery calcification when compared to co-amizolide in patients with hypertension. 78 Azelnidipine compared to the diuretic indapamide was shown to improve arterial stiffness in patients with hypertension.…”
Section: Calcification In Abdominal Aortic Aneurysm and Consequences mentioning
confidence: 99%